Smooth Muscle Specific Rac1 Deficiency Induces Hypertension by Preventing p116(RIP)(3)‐Dependent RhoA Inhibition - André, Gwennan (J Am Heart Assoc, 2014)
BACKGROUND: Increasing evidence implicates overactivation of RhoA as a critical component of the pathogenesis of hypertension. Although a substantial body of work has established that Rac1 functions antagonize RhoA in a broad range of physiological processes, the role of Rac1 in the regulation of vascular tone and blood pressure is not fully elucidated. METHODS AND RESULTS: To define the role of Rac1 in vivo in vascular smooth muscle cells (vSMC), we generated smooth muscle (SM)‐specific Rac1 knockout mice (SM‐Rac1‐KO) and performed radiotelemetric blood pressure recordings, contraction measurements in arterial rings, vSMC cultures and biochemical analyses. SM‐Rac1‐KO mice develop high systolic blood pressure sensitive to Rho kinase inhibition by fasudil. Arteries from SM‐Rac1‐KO mice are characterized by a defective NO‐dependent vasodilation and an overactivation of RhoA/Rho kinase signaling. We provide evidence that Rac1 deletion‐induced hypertension is due to an alteration of cGMP signaling resulting from the loss of Rac1‐mediated control of type 5 PDE activity. Consequently, cGMP‐dependent phosphorylation and binding of RhoA with its inhibitory partner, the phosphatase‐RhoA interacting protein (p116(RIP3)), are decreased. CONCLUSIONS: Our data reveal that the depletion of Rac1 in SMC decreases cGMP‐dependent p116(RIP3)/RhoA interaction and the subsequent inhibition of RhoA signaling. Thus, we unveil an in vivo role of Rac1 in arterial blood pressure regulation and a new pathway involving p116(RIP3) that contributes to the antagonistic relationship between Rac1 and RhoA in vascular smooth muscle cells and their opposite roles in arterial tone and blood pressure.